Radiation-induced grafting of styrene onto poly(tetrafluoroethylene) films. Part II. Properties of the grafted and sulfonated membranes - Nasef, Mohamed Mahmoud; Saidi, Hamdani; Mohd. Nor, Hussin; Ooi, Mun Foo (Society of Chemical Industry, 2000)
The physical and chemical properties of polystyrene grafted and sulfonated polytetrafluoroethylene (PTFE-graft-PSSA) membranes prepared by radiation-induced grafting of styrene onto commercial PTFE films using simultaneous irradiation technique followed by a sulfonation reaction are evaluated. The investigated properties include water uptake, ion exchange capacity, hydration number and ionic conductivity. All properties are correlated with the amount of grafted polystyrene (degree of grafting). The thermal stability of the membrane evaluated by thermal gravimetric analysis (TGA) is compared with that of original and grafted PTFE films. The membrane surface structural properties are analysed by electron spectroscopy for chemical analysis (ESCA). Membranes having degrees of grafting of 18%and above show a good combination of physical and chemical properties that allow them to be proposed for use as proton conducting membranes, provided that they have sufficient chemical and mechanical stability.